2012
DOI: 10.1016/j.exger.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Aging increases mitochondrial DNA damage and oxidative stress in liver of rhesus monkeys

Abstract: While the mechanisms of cellular aging remain controversial, a leading hypothesis is that mitochondrial oxidative stress and mitochondrial dysfunction play a critical role in this process. Here, we provide data in aging rhesus macaques supporting the hypothesis that increased oxidative stress is a major characteristic of aging and may be responsible for the age-associated increase in mitochondrial dysfunction. We measured mitochondrial DNA (mtDNA) damage by quantitative PCR in liver and peripheral blood mononu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 58 publications
4
45
0
Order By: Relevance
“…The relatively older cohort who adhered to the study would have had increased depletion of GPx activity, while supporting the increased oxidative stress expected with increasing age [68]. Depletion of GPx activity with increasing age has been previously shown in aging humans as well as in rhesus monkeys [69,70]. However, age has shown a significant positive association with RBC GPx activity in the current cohort at [71].…”
Section: Discussionmentioning
confidence: 65%
“…The relatively older cohort who adhered to the study would have had increased depletion of GPx activity, while supporting the increased oxidative stress expected with increasing age [68]. Depletion of GPx activity with increasing age has been previously shown in aging humans as well as in rhesus monkeys [69,70]. However, age has shown a significant positive association with RBC GPx activity in the current cohort at [71].…”
Section: Discussionmentioning
confidence: 65%
“…The hydroxyl radical being highly reactive can damage different macromolecules inside mitochondria like proteins, DNA and lipids [44], and that unrepaired damage to mitochondrial DNA leads to defective complex I or III which can result in increased electron reduction of O 2 to form superoxide [45][46][47]. Increased concentration of superoxide radicals that occurs due to mitochondrial DNA lesions would contribute to metabolic oxidative stress, cellular injury and genomic instability [43].…”
Section: Mitochondrial Dysfunction and Its Consequencesmentioning
confidence: 99%
“…We have previously shown that livers from healthy middle-aged and old rhesus monkeys (Macaca mulatta) show a significant reduction in mtDNA copy number, increased number of mtDNA oxidative lesions, increased lipid peroxidation and protein carbonylations, reduced antioxidant enzyme activity, and increased age-associated liver pathology (65). Recently, we found that 2 yr losartan treatment (30 mg/day) lowered serum glucose and oxidative stress markers in healthy middle-aged Rhesus monkeys without modifying blood pressure (unpublished observations).…”
Section: Ras-bl and Agingmentioning
confidence: 99%